1991
DOI: 10.1038/clpt.1991.49
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluconazole on the disposition of phenytoin

Abstract: In a randomized, placebo-controlled, parallel study, phenytoin was given in the presence and absence of fluconazole. Twenty healthy male subjects received phenytoin, 200 mg orally, on study days 1 to 3 and 18 to 20 and 250 mg intravenously on study days 4 and 21. Ten subjects received fluconazole, 200 mg orally, and 10 received placebo daily on study days 8 to 21. Serial blood samples were collected during a 24-hour period after the intravenous phenytoin dose. Fluconazole trough concentrations were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(47 citation statements)
references
References 0 publications
6
41
0
Order By: Relevance
“…The coadministration of CLO with low therapeutic index compounds in which clearance primarily depends on CYP2C19 may thus be potentially hazardous. Previous studies showed inhibitory interactions between MIC and CYP3A4, 2A6, and 2C9 in vitro and in vivo (Blum et al, 1991;Maurice et al, 1992;Black et al, 1996;Draper et al, 1997;Laine et al, 2000). Our data show that in addition to these, MIC potently inhibits CYP2C19, 2D6, 2B6, and less so CYP1A2 in vitro in cDNA-expressing microsomes.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The coadministration of CLO with low therapeutic index compounds in which clearance primarily depends on CYP2C19 may thus be potentially hazardous. Previous studies showed inhibitory interactions between MIC and CYP3A4, 2A6, and 2C9 in vitro and in vivo (Blum et al, 1991;Maurice et al, 1992;Black et al, 1996;Draper et al, 1997;Laine et al, 2000). Our data show that in addition to these, MIC potently inhibits CYP2C19, 2D6, 2B6, and less so CYP1A2 in vitro in cDNA-expressing microsomes.…”
Section: Discussionsupporting
confidence: 58%
“…In keeping with the lack of CYP3A selectivity of CLO, MIC has been shown to strongly inhibit both CYP3A and CYP2A6 in vitro (Maurice et al, 1992;Draper et al, 1997). Moreover, in vivo both fluconazole and MIC have shown to potently inhibit CYP2C9, as demonstrated by clinically significant drug interactions observed in the presence of concomitant CYP2C9 substrates, including warfarin and phenytoin (Blum et al, 1991;Black et al, 1996;Laine et al, 2000;Venkatakrishnan et al, 2000 Ballard et al, 1988). The P450 interaction profile of SUL is largely unknown, with further studies necessary.…”
mentioning
confidence: 99%
“…Therefore it is possible to speculate that fluconazole and voriconazole, but not micafungin, would clinically cause drug interactions with other drugs, which are metabolized by CYP2C9 or CYP2C19 as well as CYP3A4. It has been reported that the plasma concentrations of phenytoin and S-warfarin, which are mainly metabolized by CYP2C9, 39) are enhanced by coadministration of fluconazole, 15,46,47) and that voriconazole increases the plasma concentrations of phenytoin. 48) Mechanism-based inactivators have been reported to exhibit preincubation time dependence of inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Fluconazole is an inhibitor of the cytochrome P450 isoenzymes CYP2C9 and CYP2C19, the principal metabolising enzymes for PHT (9,133). The coadministration of fluconazole and PHT can be expected to be associated with a clinically significant increase in PHT plasma concentrations, and these may require adjustment to maintain safe therapeutic concentrations (134). Most of the second-generation AEDs, such as VGB, LTG, TGB, LEV, OXC, ZNS, and GBP, are not substrates of either CYP2C9 or CYP2C19 and are therefore unlikely to interact with fluconazole.…”
Section: Antifungal Agentsmentioning
confidence: 99%